2017
DOI: 10.3389/fnhum.2016.00664
|View full text |Cite
|
Sign up to set email alerts
|

Can the Psycho-Emotional State be Optimized by Regular Use of Positive Imagery?, Psychological and Electroencephalographic Study of Self-Guided Training

Abstract: The guided imagery training is considered as an effective method and therefore widely used in modern cognitive psychotherapy, while less is known about the effectiveness of self-guided. The present study investigated the effects of regular use of self-guided positive imagery, applying both subjective (assessment of the psycho-emotional state) and objective (electroencephalographic, EEG) approaches to research. Thirty healthy subjects participated in the cognitive imagery-training program for 12 weeks. The sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
4
6
0
Order By: Relevance
“…This work confirmed the results obtained in our previous study (Velikova et al, 2017 ) that self-guided positive imagery training, implemented in accordance with the protocol described, had a positive impact on the emotional state of participants, they were more satisfied with their lives, and they perceived themselves as more effective. For all tests no significant differences were observed between the performances during baseline (E 0 ) and pre-training (E 1 ) examinations, therefore the effects should not be explained by the repetition of the tasks.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This work confirmed the results obtained in our previous study (Velikova et al, 2017 ) that self-guided positive imagery training, implemented in accordance with the protocol described, had a positive impact on the emotional state of participants, they were more satisfied with their lives, and they perceived themselves as more effective. For all tests no significant differences were observed between the performances during baseline (E 0 ) and pre-training (E 1 ) examinations, therefore the effects should not be explained by the repetition of the tasks.…”
Section: Discussionsupporting
confidence: 91%
“…The non-verbal reasoning was a unique domain where significant changes were observed only in half of the sample without depressive symptomatology. A possible explanation may be consistent with the study (Takesaki et al, 2016 ), demonstrating a positive relationship between functional connectivity and non-verbal reasoning, and although we did not study functional connectivity here, our previous study of emotional images (Velikova et al, 2017 ) demonstrated an increased communication after training. On the other hand it known that capacity to imagine is reduced in presence of depressive symptomatology (Hackmann et al, 2011 ).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations